ANALISIS PENDAPATAN USAHATANI BUAH RAMBUTAN DI DESA TALAWAAN KABUPATEN MINAHASA UTARA - Wa Ode Ariany; Gene H. M. Kapantow; Caroline B. D. Pakasi (Sam Ratulangi University, 2016)
Rambutan (Nephelium lappaceum L) in the form of a tree with fruit that has skin hair resembles a fruit crop wooded meant in the family Sapindaceae. Talawaan village is a center of rambutan fruit producer in North Minahasa Regency. This research was conducted in January to April 2016 in the village Talawaan Talawaan District of North Minahasa regency. This study using purposive sampling technique using a sample of 15 people rambutan growers. Data collected consist of primary data and secondary data. The results showed that the respondents farmers for the production of rambutan Talawaan village average per farmer as much as 1237.73 kg while the average production per tree as much as 78.51 kg with the average price per kilogram of rambutan Rp 6,000. Rambutan farm receipts on average per farmer Rp 7.4264 million while for the average receipts per tree Rp 471 060. Farm production costs to the cost of production per farmer Rp 228.374.33 while the cost of production per tree Rp 161.56.78, so revenues are reduced by the cost of production, the rambutan farm income to average per farmer Rp 7,198,025.67 while for earnings per tree Rp 454,904.63.